Inhibition of cortical somatosensory processing during and after low frequency peripheral nerve stimulation in humans. Issue 7 (July 2021) - Hewitt, Danielle; Byrne, Adam; Henderson, Jessica; Newton-Fenner, Alice; Tyson-Carr, John; Fallon, Nicholas; Brown, Christopher; Stancak, Andrej
Highlights: Low frequency electrical stimulation of the peripheral nerve has concurrent and post-stimulation effects on cortical activity. Source activity in the midcingulate and operculo-insular cortex decline linearly during low frequency stimulation. Low frequency stimulation attenuates neural responses to noxious laser stimuli and enhances resting alpha and beta band power. Abstract: Objective: Transcutaneous low-frequency stimulation (LFS) elicits long-term depression-like effects on human pain perception. However, the neural mechanisms underlying LFS are poorly understood. We investigated cortical activation changes occurring during LFS and if changes were associated with reduced nociceptive processing and increased amplitude of spontaneous cortical oscillations post-treatment. Methods: LFS was applied to the radial nerve of 25 healthy volunteers over two sessions using active (1 Hz) or sham (0.02 Hz) frequencies. Changes in resting electroencephalography (EEG) and laser-evoked potentials (LEPs) were investigated before and after LFS. Somatosensory-evoked potentials were recorded during LFS and source analysis was carried out. Results: Ipsilateral midcingulate and operculo-insular cortex source activity declined linearly during LFS. Active LFS was associated with attenuated long-latency LEP amplitude in ipsilateral frontocentral electrodes and increased resting alpha (8–12 Hz) and beta (16–24 Hz) band power in electrodes overlying operculo-insular, sensorimotor and frontal cortical regions. Reduced ipsilateral operculo-insular cortex source activity during LFS correlated with a smaller post-treatment alpha-band power increase. Conclusions: LFS attenuated somatosensory processing both during and after stimulation. Significance: Results further our understanding of the attenuation of somatosensory processing both during and after LFS.